2013
DOI: 10.3174/ajnr.a3620
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diffusivity in the Anterior Lobe of the Pituitary Gland: 3D Turbo Field Echo with Diffusion-Sensitized Driven-Equilibrium Preparation

Abstract: BACKGROUND AND PURPOSE: 3D turbo field echo with diffusion-sensitized driven-equilibrium preparation is a non-echo-planar technique for DWI, which enables high-resolution DWI without field inhomogeneity-related image distortion. The purpose of this study was to evaluate the feasibility of diffusion-sensitized driven-equilibrium turbo field echo in evaluating diffusivity in the normal pituitary gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…The details of the DSDE-TFE are described elsewhere. 9,[15][16][17] The DSDE-TFE has two distinct components: the DSDE preparation and the segmented 3D TFE data acquisition. 17 The DSDE preparation is an extension of a motionsensitized driven-equilibrium (MSDE) preparation, which has been used for black-blood imaging of large vessels.…”
Section: Imaging Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The details of the DSDE-TFE are described elsewhere. 9,[15][16][17] The DSDE-TFE has two distinct components: the DSDE preparation and the segmented 3D TFE data acquisition. 17 The DSDE preparation is an extension of a motionsensitized driven-equilibrium (MSDE) preparation, which has been used for black-blood imaging of large vessels.…”
Section: Imaging Techniquementioning
confidence: 99%
“…2,5 Diffusion-weighted imaging (DWI) is widely used to diagnose tumours, inflammation and vascular disease in both intracranial and extracranial lesions. 3,4,[6][7][8][9][10][11][12][13][14][15][16] Previous studies also revealed the efficacy of DWI to evaluate orbital lesions including orbital tumours of adults 8,9 and children, 10 ocular adnexal lymphomas, 9,11 immunoglobulin G4 (IgG4)-related disease, 9 endophthalmitis 12 and optic nerve lesions. 13,14 However, it is sometimes difficult to evaluate intraorbital structures with echoplanar (EP) imaging, which is the most common imaging technique for DWI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…n this issue of the American Journal of Neuroradiology, you will find the article "Evaluation of Diffusivity in the Anterior Lobe of the Pituitary Gland: 3D Turbo Field Echo with Diffusion-Sensitized Driven-Equilibrium Preparation" by Hiwatashi et al 1 I enjoyed reading this article and found it to be a nice "proof of principle" regarding the use of "diffusion-sensitized driven-equilibrium turbo field echo" to image the anterior pituitary gland. 1 In my clinical practice, I have found diffusion-weighted imaging to have particular utility in neuroimaging…well beyond the classic assessment for acute brain ischemia or infarction or pyogenic abscess formation.…”
mentioning
confidence: 99%
“…1 In my clinical practice, I have found diffusion-weighted imaging to have particular utility in neuroimaging…well beyond the classic assessment for acute brain ischemia or infarction or pyogenic abscess formation. I like the idea of "squeezing out" as much information as possible from each of our MR images to help identify and characterize neuropathology.…”
mentioning
confidence: 99%